Students’ Perceptions on the Use of Google Docs as an Online Collaborative Tool in Translation Class - Sudrajat, Winny Nur Ardy; Purnawarman, Pupung (Lingua Cultura, 2019)
The research aimed at investigating students’ perceptions and experiences of using Google Docs in the translation class. Google Docs provided characteristics that can be used to promote peer interaction. However, the use of Google Docs as teaching and learning media was rarely conducted and still limited to teaching writing in Indonesia. Google Docs was commonly used by the translator to translate collaboratively, so the students worked together in a small group to solve and discuss the translation assignment by using some features through Google Docs. These activities were expected to enhance collaboration among them. This research employed a qualitative descriptive study as the research design. The questionnaire was used as the instrument to collect the data that involved fifty students (N = 50) as the participant. The results of this research show that students have a positive response to the use of Google Docs in translation class. It indicates that Google Docs is a suitable tool that can be used for educational purposes.